2014
DOI: 10.1111/apa.12581
|View full text |Cite
|
Sign up to set email alerts
|

Antisecretory factor effectively and safely stops childhood diarrhoea: a placebo‐controlled, randomised study

Abstract: Aim: We studied the response to high doses of egg yolk containing antisecretory factor (B221 â , Salovum â ) in young children with acute diarrhoea, presenting to the Children's Hospital, Lahore, Pakistan.Methods: In a randomised, placebo-controlled trial, 36 children aged 7 to 60 months with acute diarrhoea of unknown aetiology, with mild-to-moderate dehydration, were randomised to the Salovum â or placebo groups. Initially, 16 grams of Salovum â or ordinary egg yolk (placebo) mixed in oral rehydration salts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…The dosage of Salovum and the dosage interval were chosen from the lower ranges of dosages as reported from prior human trials with Salovum (19).…”
Section: Administration Of Salovummentioning
confidence: 99%
“…The dosage of Salovum and the dosage interval were chosen from the lower ranges of dosages as reported from prior human trials with Salovum (19).…”
Section: Administration Of Salovummentioning
confidence: 99%
“…We have previously shown that peroral treatment of children with Salovum effectively counteracts diarrheal diseases of various etiologies (Zaman et al, 2014;Zaman et al, 2013;Zaman et al, 2007). A registration of the children's health status, with a focus on diarrheal diseases recurrence during the diarrhea rehabilitation period has, however, not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…A modified egg-yolk product enriched with antisecretory factor (Salovum®, AS-Faktor AB, Sweden) reduced the duration of acute and prolonged (>7 days) diarrhoea in a randomized, placebo-controlled trial in children aged 7–60 months. 129 Further clinical and mechanistic studies are needed for this promising drug.…”
Section: New Antidiarrhoeal Therapiesmentioning
confidence: 99%